2021
DOI: 10.1080/19490976.2021.1939599
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal carriage of Klebsiella pneumoniae in a general adult population: a cross-sectional study of risk factors and bacterial genomic diversity

Abstract: Antibiotic resistant Klebsiella pneumoniae is a leading public health threat and gastrointestinal carriage is an established risk factor for subsequent infections during hospitalization. Our study contributes new knowledge of risk factors for gastrointestinal carriage and the genomic population structure of K. pneumoniae colonizing humans in a representative sample of a general population in a community setting. Altogether, 2,975 participants (54% women) >40 y in the population-based Tromsø Study: Tromsø7, Nor… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
57
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 48 publications
(66 citation statements)
references
References 57 publications
7
57
1
1
Order By: Relevance
“…These isolates comprise a set of diverse K. pneumoniae , represented by many STs in both animal species. Many of these STs, such as ST13, ST17, ST35, ST37 and ST290, have previously been identified in humans ( Marcade et al, 2013 ; Safavi et al, 2020 ; Raffelsberger et al, 2021 ). A recently published study from Norway screened 2,975 healthy persons for K. pneumoniae gut carriage ( Raffelsberger et al, 2021 ), and identified a diverse population of K. pneumoniae .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These isolates comprise a set of diverse K. pneumoniae , represented by many STs in both animal species. Many of these STs, such as ST13, ST17, ST35, ST37 and ST290, have previously been identified in humans ( Marcade et al, 2013 ; Safavi et al, 2020 ; Raffelsberger et al, 2021 ). A recently published study from Norway screened 2,975 healthy persons for K. pneumoniae gut carriage ( Raffelsberger et al, 2021 ), and identified a diverse population of K. pneumoniae .…”
Section: Discussionmentioning
confidence: 99%
“…Many of these STs, such as ST13, ST17, ST35, ST37 and ST290, have previously been identified in humans ( Marcade et al, 2013 ; Safavi et al, 2020 ; Raffelsberger et al, 2021 ). A recently published study from Norway screened 2,975 healthy persons for K. pneumoniae gut carriage ( Raffelsberger et al, 2021 ), and identified a diverse population of K. pneumoniae . The study also identified ST35 and ST37 among the most common STs identified in healthy Norwegians, although the occurrence of these STs were found to be only 1.9% each ( Raffelsberger et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations